The Knowledge, Attitudes and Behaviours About Family Planning and Optional Abortion of The Women and of Their Husbands Who Applied To Elaziğ State Hospital Family Planning Polyclinic in Order To Make Induced Abortion - Güngör, Leyla; Açık, Yasemin; Güngör, M. Yüksel; Oğuzöncül, A. Ferdane (Fırat University, 2003)
Aim: This study were carried out in order to determine the knowledge, attitudes and behaviours about family planning (FP) and abortion of the women and of their husbands who applied to Elazığ State Hospital Family Planning for the purpose of making optional abortion. Mataerial and method: Total 196 couples (196 males and 196 females) were included in the study. Questionnaire method was used to obtain the data, and X2 test was utilised for statistic analyses. Results: Of the research group, 46.4% of the women and 29.6% of the men expressed that FP services were available from Health Departments. Men and women, suggested that they know mostly IUD, drug, condom and coitus interruptus of FP method. The mean number of optional abortion was 1.7±1.1for the women participated in the study. 36.7% of the males and 26.5% of the females described optional obortion as a FP method. 24.5% of females and 17.9% of males expressed that induced abortion should be prohibited. 89.9% of the women were applied any FP method and the most preferable method was IUD at a rate of 54.6%. 10 days after the optional abortion, 56.6% of the women came to the hospital for control. Conclusion: Consequently, the women and their husbands who applied to Elazığ State Hospital Family Planning Polyclinic in order to make induced abortion knew the FP methods at a significant level. Besides, they applied optional abortion in high rates.

Amaç: Bu çalışma; Elazığ Devlet Hastanesi Aile Planlaması Polikliniğine (EDHAPP) isteğe bağlı düşük yapmak için başvuran kadınların ve eşlerinin, aile planlaması (AP) ve düşük hakkındaki bilgi, tutum ve davranışlarının tespit edilmesi amacıyla yapılmıştır. Gereç ve yöntem: 196 erkek, 196 kadın araştırma kapsamına alınmıştır. Verilerin elde edilmesinde anket yöntemi ve istatistiksel analizlerde X2 kullanılmıştır. Bulgular: Kadınların %46.4'ü, erkeklerin %29.6'sı AP hizmetlerinin sağlık ocaklarından alınabileceğini belirtmişlerdir. Kadınlar ve erkekler korunma yöntemlerinden en fazla RİA'yı, hapı, kondomu ve geri çekmeyi bildiklerini ifade etmişlerdir. Kadınların ortalama istemli düşük sayısı 1.7±1.1'dir. Erkeklerin %36.7'si, kadınların %26.5'i, isteğe bağlı düşüğü bir AP yöntemi olarak tanımlamıştır. Kadınların %24.5'i, erkeklerin %17.9'u istemli düşüğün yasaklanması gerektiğini ifade etmiştir. Düşük sonrası kadınların %89.8'i herhangi bir AP yöntemini almış ve en fazla tercih edilen yöntem %54.6 ile RİA olmuştur. %56.6'sı istemli düşükten 10 gün sonra kontrole gelmiştir. Sonuç: Sonuç olarak, EDHAPP'ne istemli düşük yapmak için başvuran kadınlar ve eşleri AP yöntemlerini önemli düzeyde bilmişlerdir. Bunun yanı sıra istemli düşüğe de yüksek oranlarda başvurmuşlardır.
Elazığ Devlet Hastanesi Aile Planlaması Polikliniğine İsteğe Bağlı Düşük Yapmak İçin Başvuran Kadınlar ve Eşlerinin Aile Planlaması ve İsteğe Bağlı Düşük Hakkındaki Bilgi, Tutum, Davranışları